2003
DOI: 10.1007/s11906-003-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin system in blacks: Active, passive, or what?

Abstract: Plasma renin activity in blacks has been consistently reported to be lower than in whites. Many mechanisms for the low plasma renin activity have been proposed, including volume status, renal sodium handling, and the reduction of renin release. The status of the RAS is paramount in the regulation of salt and water balance and its implications in disease processes such as hypertension and renal failure. In this review, we present data to suggest that low systemic plasma renin activity in blacks may not be the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
3
23
1
Order By: Relevance
“…In our total HyperPATH cohort study, we confirmed that ALDO, PRA, and potassium levels on a LIB salt diet were lower in AD than ED, as has been shown by others (1)(2)(3)(4)(5)(6)24). Because of limited genotyping data, we also performed analyses in a 2:1 restricted subcohort.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our total HyperPATH cohort study, we confirmed that ALDO, PRA, and potassium levels on a LIB salt diet were lower in AD than ED, as has been shown by others (1)(2)(3)(4)(5)(6)24). Because of limited genotyping data, we also performed analyses in a 2:1 restricted subcohort.…”
Section: Discussionsupporting
confidence: 85%
“…Compared with persons of European descent (ED), individuals of African descent (AD) are known to: (i) be more susceptible to cardiovascular disease (CVD); (ii) have a greater frequency of hypertension (HTN) (particularly salt-sensitive HTN); (iii) have more cardiovascular (CV) damage with HTN; (iv) have lower plasma renin activity (PRA); and (v) more resistant HTN (1)(2)(3)(4)(5)(6). Of interest, these same characteristics also are associated with increased aldosterone (ALDO) production, e.g., primary aldosteronism.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension has been shown to increase the risk of microalbuminuria in the absence of diabetes (13,15), and racial and ethnic differences in the risk of hypertension are known to exist (45,46,55,56). Numerous mechanisms have been described to account for racial and ethnic differences in risk of hypertension (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74), including increased salt sensitivity in blacks (75) and Asians (57), low renin-angiotensin responsiveness in blacks (58,65), decreased excretion of potassium (76), and differences in renal vasculature and nephron number, although controversy exists regarding some proposed mechanisms (77,78). The current study found that prevalent hypertension was associated with a 1.9-fold greater odds of macroalbuminuria (OR 1.94; 95% CI 1.20 to 3.13) and trended toward increased odds of microalbuminuria (OR 1.25; 95% CI 0.97 to 1.62); however, when models were stratified by diagnosis of hypertension, blacks and Hispanics were more likely to have micro-or macroalbuminuria in the presence of hypertension, whereas Asian patients were more likely to have micro-or macroalbuminuria in the absence of a diagnosis of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic factors include excess obesity, more salt sensitivity, higher vascular resistance, endothelium-dependent and independent vascular dysfunction, greater arteriolar remodelling and, despite a tendency toward lower circulating renin activity, greater activation of the local renin-angiotensin-aldosterone system compared with whites. [5][6][7][8][9] There is also a lesser nocturnal decline in BP (non-dipping) and therefore higher nocturnal BP levels in blacks compared with whites. 10,11 Sustained environmental exposureshigh dietary sodium and low dietary potassium and possibly calcium intakes-as well obesity, diabetes and CKD all plausibly contribute to both elevated BP levels as well as to the abnormal diurnal variation in BP.…”
Section: Introductionmentioning
confidence: 99%